A photoenzyme catalyst, preparation method and application thereof
By immobilizing graphite phase carbon nitride and horseradish peroxidase on the nanoflower structure, a photoenzyme catalyst was formed, which solved the problems of long acridine degradation time and media toxicity, and achieved efficient and environmentally friendly acridine degradation effect. Secondary contamination is avoided and the stability and reusability of the catalyst are maintained.
Patent Information
- Application Number
- CN202211678890.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2022-12-26
- Publication Date
- 2024-12-27
- Estimated Expiration
- 2042-12-26
AI Technical Summary
The prior art has problems of excessive degradation time, media toxicity and secondary pollution during the acridine degradation process, and requires additional costs and resources.
The graphite phase carbon nitride (g-C3N4) and horseradish peroxidase (HRP) were combined to immobilize the nanoflower structure, and the acridine was degraded in visible light through photoenzyme coupling catalyst, avoiding secondary pollution to the environment and Shorten the degradation time.
The 99.9% degradation rate of acridine was achieved within 3 hours, avoiding additional costs and pollution, and the catalyst maintained good activity in a wide range of acid and alkali and temperatures, with good stability and reusability.
Smart Images

Figure CN116174003B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the field of enzyme catalytic degradation, and in particular to a photoenzyme catalyst, a preparation method thereof and application thereof. Background Art
[0002] Nitrogen-containing heterocyclic compounds, such as acridine (also known as 10-azaanthracene, dibenzopyridine), are widely present in industrial wastewaters such as coking wastewater, dye wastewater, pharmaceutical wastewater, pesticide wastewater, and soil and groundwater around wood preservative treatment sites. Compared with aliphatic or aromatic compounds, nitrogen-containing heterocyclic compounds are not easily decomposed through metabolic processes, their biodegradability is also poor, and they have teratogenic, carcinogenic and mutagenic properties, posing potential hazards to the environment and human health. In view of this, in-depth and innovative research on the degradation technology of nitrogen-containing heterocyclic compounds is the key to solving this type of wastewater pollution problem.
[0003] The document (Colloids Surf B Biointerfaces, 2020, 196, 111348) discloses a method for the degradation of acridine, which is assembled by co-immobilization of the encapsulation medium 2,2′-azidobis(3-ethylbenzothiazoline-6-sulfonate) (ABTS) by grafting glycidyl methacrylate and dopamine into functionalized calcium alginate composite beads, and then covalently immobilizing laccase to the beads for the degradation of acridine. According to the test, the degradation rate of acridine in 8 hours is about 100%. However, the mediator ABTS used in the document is toxic in itself, and although the mediator is fixed in the functionalized calcium alginate composite beads, it still has the possibility of falling off, which will cause secondary pollution to the environment. Moreover, although the degradation rate of acridine reported in the document is very high, the degradation time is too long.
[0004] Patent document CN115093017A immobilizes horseradish peroxidase (HRP) and glucose oxidase (GOD) on dopamine-modified cellulose-chitosan composite beads by covalent bonding for the degradation of acridine. According to the test, the degradation rate of acridine can reach 99.5% in 8 hours. The acridine degradation method disclosed in CN115093017A requires additional glucose to activate the reaction, which leads to additional costs and secondary pollution to the water body. On the other hand, the document also requires 8 hours to achieve complete degradation of acridine.
[0005] In view of this, how to shorten the degradation time of acridine and improve the degradation efficiency while ensuring a high degradation rate of acridine, while avoiding the problems existing in the prior art, is a technical problem that needs to be solved urgently by those skilled in the art. Summary of the invention
[0006] Graphitic carbon nitride (gC 3 N 4) is a new type of non-metallic semiconductor photocatalytic material with excellent photoelectrochemical properties, good stability, and outstanding biocompatibility. It produces H 2 O 2 .
[0007] The present invention is designed to combine HRP and gC 3 N 4 The invention is completed by combining the preparation technology of inorganic nanoflowers and performing photoenzyme coupled catalytic reaction for the degradation of nitrogen-containing heterocyclic compounds.
[0008] One object of the present invention is to provide a photoenzyme catalyst to achieve effective and efficient degradation of nitrogen-containing heterocyclic compounds, such as acridine. Other objects of the present invention also include providing a method for preparing the photoenzyme catalyst and the use of the photoenzyme catalyst in degrading nitrogen-containing heterocyclic compounds, such as acridine.
[0009] To achieve the above object, the present invention provides a photoenzyme catalyst in a first aspect, which has a nanoflower structure, and the nanoflower structure is fixed with gC 3 N 4 and HRP.
[0010] In some embodiments, in the photoenzyme catalyst, gC 3 N 4 The mass ratio of hydroxylamine to HRP is (0.5-3):1, preferably (1-3):1, further preferably (1.5-3):1, and most preferably 1.5:1.
[0011] In some embodiments, the nanoflower structure contains divalent copper ions and phosphate ions.
[0012] In some embodiments, the photoenzyme catalyst is prepared by adding copper sulfate to a solution containing gC 3 N 4 and HRP in phosphate buffered saline.
[0013] The second aspect of the present invention provides a method for preparing the aforementioned photoenzyme catalyst, comprising:
[0014] Formulated with gC 3 N 4 , HRP, a reaction mixture of a phosphate buffer solution of a divalent copper salt,
[0015] The reaction mixture is allowed to react at 0-10°C for 12-36 hours,
[0016] After the reaction is completed, the photoenzyme catalyst is separated and obtained.
[0017] The invention forms a nano flower structure by inorganic hybridization of metal copper ions, phosphate ions and proteins.
[0018] In some embodiments, the reaction mixture comprises gC 3 N 4 The composition of the invention is a phosphate buffer solution containing HRP, divalent copper salt.
[0019] In some embodiments, in the reaction mixture, gC 3 N 4 The mass ratio of hydroxylamine to HRP is (0.5-3):1, preferably (1-3):1, further preferably (1.5-3):1, and most preferably 1.5:1.
[0020] In some embodiments, in the reaction mixture, the concentration ratio of divalent copper ions to phosphate is 1:(15-25).
[0021] In some embodiments, in the reaction system, the gC 3 N 4 The concentration of is 0.125-0.75 mg / mL, the concentration of HRP is 0.25 mg / mL, the concentration of divalent copper ions is 10 mM, and the concentration of phosphate buffer solution is 190 mM.
[0022] In some embodiments, the divalent copper salt is copper sulfate.
[0023] The third aspect of the present invention provides the use of the aforementioned photoenzyme catalyst in catalytic degradation of nitrogen-containing heterocyclic compounds, wherein the nitrogen-containing heterocyclic compound is preferably acridine.
[0024] A fourth aspect of the present invention provides the use of the aforementioned photoenzyme catalyst in treating wastewater containing nitrogen heterocyclic compounds, wherein the nitrogen heterocyclic compound is preferably acridine.
[0025] In some embodiments, the photoenzyme catalyst is capable of degrading more than 99% of nitrogen-containing heterocyclic compounds within 3 hours. Beneficial Effects
[0026] 1. The present invention will gC 3 N 4 and HRP are fixed on the nanoflower structure to obtain a photoenzyme catalyst that can perform photoenzyme coupling catalytic reaction. After testing, the photoenzyme catalyst provided by the present invention can basically completely degrade acridine into CO 2 and H 2 O, thus achieving complete mineralization of acridine. The degradation efficiency can reach 99.9% within 3 hours.
[0027] 2. The photoenzyme catalyst provided by the present invention has a fixed gC3 N 4 H can be generated in situ under visible light 2 O 2 , no need to add H during the degradation reaction 2 O 2 Or add other 2 O 2 substances, thereby avoiding secondary pollution to the environment.
[0028] 3. The photoenzyme catalyst provided by the present invention can not only maintain good catalytic degradation activity, but also has good stability and environmental tolerance, and exhibits optimal activity in a wide range of acidity, alkali and temperature; the photoenzyme catalyst can be recycled by centrifugation and filtration, and its catalytic activity remains at a high level after 5 cycles of use.
[0029] 4. The use of the catalyst provided by the present invention to degrade acridine has the advantages of simple operation method, low cost, green and environmental protection, and obvious degradation effect on acridine, and has good economic prospects and practical value. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 Middle 1 and a 2 b is the SEM image of HRP nanoflowers at different scales; b 1 and b 2 SEM images of the photoenzyme catalyst prepared in Example 1 at different scales; c 1 and c 2 gC at different scales 3 N 4 SEM image of nanoflowers.
[0031] Figure 2 gC 3 N 4 Nanoflower (a) and gC prepared in Example 1 3 N 4 / HRP photoenzyme catalyst (b) XRD pattern.
[0032] Figure 3 gC 3 N 4 Nanoflower (a), gC prepared in Example 1 3 N 4 FT-IR images of / HRP photoenzyme catalyst (b) and HRP nanoflowers (c).
[0033] Figure 4 It shows that during the preparation of the catalyst gC 3 N 4 Effect of the mass ratio of HRP / HRP on the degradation efficiency.
[0034] Figure 5 The effect of the pH value of the wastewater to be treated on the degradation efficiency of acridine is shown.
[0035] Figure 6 The effect of temperature on the degradation efficiency of acridine during the degradation treatment is shown.
[0036] Figure 7 The degradation efficiency of the photoenzyme catalyst provided by the present invention within five cycles is shown. DETAILED DESCRIPTION
[0037] In order to have a clearer understanding of the technical solution, purpose and effect of the present invention, the specific implementation mode of the present invention is now described in conjunction with the accompanying drawings.
[0038] It should be noted that, if no specific conditions are specified in the following examples, the experiments were carried out under conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used, if no manufacturer is specified, are all conventional products that can be purchased commercially.
[0039] C 3 N 4 Preparation
[0040] Melamine was placed in a crucible, and then placed in a muffle furnace and heated to 550°C at a heating rate of 2.5°C / min, and calcined for 4 h. The calcined product was then washed with anhydrous ethanol and deionized water, and dried. The dried product was ground and placed in a muffle furnace and heated to 500°C at a heating rate of 5°C / min, and calcined for 2 h to obtain gC 3 N 4 .
[0041] Example 1 Preparation of Photoenzyme Catalyst (gC 3 N 4 :HRP=1.5:1)
[0042] Weigh 7.5 mg gC 3 N 4 5 mg of HRP were dispersed in 19 mL of pH = 7.4, 200 mM PBS buffer (the concentration of the PBS solution is the concentration of phosphate in it) and stirred for 2 h. 1 mL of 200 mM CuSO 4 After the solution was mixed evenly, the mixture was immobilized and reacted at 4 °C for 24 h. After the reaction, the solid was separated by centrifugation at 8000 rpm for 5 min, and then washed with deionized water three times to obtain the photoenzyme catalyst (also called gC 3 N 4 / HRP photoenzyme catalyst).
[0043] Example 2 Preparation of Photoenzyme Catalyst (gC 3 N 4 :HRP=0.5:1)
[0044] The preparation method of Example 2 is different from that of Example 1 only in that 7.5 mg gC in Example 1 is used as 3 N 4 Replaced with 2.5 mg gC 3 N 4 .
[0045] Example 3 Preparation of Photoenzyme Catalyst (gC 3 N 4 :HRP=1:1)
[0046] The preparation method of Example 3 is different from that of Example 1 only in that 7.5 mg gC 3 N 4 Replaced with 5mg gC 3 N 4 .
[0047] Example 4 Preparation of Photoenzyme Catalyst (gC 3 N 4 :HRP=2:1)
[0048] The preparation method of Example 4 is different from that of Example 1 only in that 7.5 mg gC in Example 1 is used as 3 N 4 Replaced with 10 mg gC 3 N 4 .
[0049] Example 5 Preparation of Photoenzyme Catalyst (gC 3 N 4 :HRP=2.5:1)
[0050] The preparation method of Example 5 differs from that of Example 1 only in that 7.5 mg gC 3 N 4 Replaced with 12.5 mg gC 3 N 4 .
[0051] Example 6 Preparation of Photoenzyme Catalyst (gC 3 N 4 :HRP=3.0:1)
[0052] The preparation method of Example 6 differs from that of Example 1 only in that 7.5 mg gC 3 N 4 Replaced with 15 mg gC 3 N 4 .
[0053] In addition, for the convenience of characterization and analysis, HRP nanoflowers and gC 3 N 4 The preparation method of HRP nanoflowers differs from that of Example 1 only in that gC is not added during the preparation process. 3 N 4 ;gC 3 N 4 The difference between the preparation method of nanoflowers and Example 1 is that gC is not added during the preparation process.3 N 4 HRP.
[0054] Characterization Example 1 Scanning Electron Microscope (SEM) Characterization
[0055] Scanning electron microscopy (SEM) was used to characterize the gC prepared in Example 1. 3 N 4 / HRP photoenzyme catalyst structure and morphology, the results are as follows Figure 1 shown.
[0056] from Figure 1 It can be seen that HRP nanoflowers, gC 3 N 4 / HRP photoenzyme catalyst and gC 3 N 4 Nanoflowers are uniformly dispersed spherical nanoflower structures assembled from hundreds of nanoplates.
[0057] Characterization Example 2 X-ray diffraction (XRD) characterization
[0058] X-ray diffraction (XRD) was used to characterize the gC prepared in Example 1. 3 N 4 / HRP photoenzyme catalyst analysis, the results are as follows Figure 2 As shown, in Figure 2 In the figure, curve (a) is gC 3 N 4 XRD diagram of nanoflowers, curve (b) is the gC prepared in Example 1 3 N 4 / HRP photoenzyme catalyst XRD pattern. Figure 2 It can be seen that gC 3 N 4 / HRP photoenzyme catalyst has a weak diffraction peak at 27.7°, corresponding to gC 3 N 4 The interlayer aromatic filling structure plane (002) is formed. The results show that gC 3 N 4 Successfully introduced gC 3 N 4 / HRP photoenzyme catalyst.
[0059] Characterization Example 3 Fourier Transform Infrared Spectrometer (FT-IR) Characterization
[0060] The molecular structure of the catalyst was characterized by Fourier transform infrared spectroscopy (FT-IR). −1 The weak peak at comes from the amide carbonyl in HRP. Compared with HRP nanoflowers, gC 3 N 4 / HRP photoenzyme catalyst at 1200-1600 cm−1 There are a series of diffraction peaks in the range, which are caused by gC 3 N 4 Among them, 1540~1635 cm −1 The series of bands at 1239-1460 cm −1 The peak at is the aromatic CN heterocyclic pattern. The results show that HRP and gC 3 N 4 All have been successfully introduced into gC 3 N 4 / HRP photoenzyme catalyst.
[0061] Taking acridine as an example, the gC 3 N 4 The degradation performance of gC / HRP photoenzyme catalysts towards nitrogen-containing heterocyclic compounds was evaluated by degradation of acridine under a xenon lamp with a 400 nm filter. 3 N 4 / Performance of HRP photoenzyme catalyst.
[0062] First, the general testing process is described.
[0063] (1) Prepare simulated wastewater with an acridine concentration of 10 mg / L, add the simulated wastewater to a reactor, and use the gC prepared in Example at a certain temperature. 3 N 4 / HRP photoenzyme catalyst degradation of acridine, the solution was stirred in the dark for 30 min to balance adsorption-desorption, and then the photocatalytic reaction was carried out under a 300 W xenon lamp and a 420 nm cutoff filter for several hours. After the reaction was completed, the gC 3 N 4 / HRP photoenzyme catalyst.
[0064] (2) The acridine content in the degraded simulated wastewater was detected by high performance liquid chromatography. Before injection into the chromatographic column, the sample was filtered with a 0.45 μm filter.
[0065] The chromatographic conditions were as follows:
[0066] Chromatographic column: C18 column;
[0067] Mobile phase: methanol: water = 8:2;
[0068] Detector: fluorescence detector;
[0069] The detection wavelength was 250 nm;
[0070] Flow rate is 1-2 mL / min;
[0071] The injection volume was 10 μL.
[0072] (3) The calculation formula of acridine degradation rate is as follows:
[0073] D(%)=[(C 0 −C t ) / C 0 ]×100%
[0074] Where, D is the degradation rate of acridine, C 0 is the initial concentration of acridine, C t is the concentration of acridine after degradation.
[0075] Test Example 1: Investigation of gC in Catalyst 3 N 4 Effect of the mass ratio of HRP to Acridine on the degradation of Acridine
[0076] Prepare simulated wastewater with an acridine concentration of 10 mg / L and a pH of 7.0, take 15 mL of the simulated wastewater and add it to a 30 mL reactor, then add 10 mg of gC prepared in Example 1-6 respectively. 3 N 4 / HRP photoenzyme catalyst, under the reaction conditions of 20 ° C and 200 r / min, the solution was stirred in the dark for 30 min to balance the adsorption-desorption, and then the photocatalytic reaction was carried out under a 300 W xenon lamp and a 420 nm cutoff filter for 0.5-3 hours. After the reaction, the gC 3 N 4 / HRP photoenzyme catalyst.
[0077] Then, the above-mentioned high performance liquid chromatography method was used for detection, and the above-mentioned acridine degradation rate calculation formula was used to calculate the acridine content in the simulated wastewater after degradation. The test results are as follows: Figure 4 shown.
[0078] from Figure 4 It can be seen that during the preparation of the catalyst, as gC 3 N 4 The degradation efficiency of acridine increases with the increase of mass ratio relative to HRP. 3 N 4 When the mass ratio of gC / HRP is 1.5, the degradation efficiency reaches a maximum of 99.9% after 3 h of reaction. 3 N 4 As the mass ratio of gC to HRP continued to increase, the degradation efficiency of acridine decreased slightly. 3 N 4 When the mass ratio of HRP to HRP is (0.5-3):1, preferably (1-3):1, further preferably (1.5-3):1, and most preferably 1.5:1, a relatively satisfactory catalytic degradation effect can be achieved.
[0079] Test Example 2: Investigating the effect of wastewater pH on acridine degradation
[0080] According to the results of Test Example 1, the photoenzyme catalyst (gC 3 N 4 :HRP=1.5:1) to further investigate the effect of wastewater pH on the degradation of acridine.
[0081] Prepare simulated wastewater with an acridine concentration of 10 mg / L and a pH of 5, 6, 7, 8, and 9, respectively. Take 15 mL of the simulated wastewater and add it to a 30 mL reactor. Then, add 10 mg of gC prepared in Example 1, respectively. 3 N 4 / HRP photoenzyme catalyst, under the reaction conditions of 25 ℃ and 200 r / min, the solution was stirred in the dark for 30 min to balance the adsorption-desorption, and then the photocatalytic reaction was carried out under a 300 W xenon lamp and a 420 nm cutoff filter for 0.5-3 hours. After the reaction, the gC 3 N 4 / HRP photoenzyme catalyst.
[0082] Then, the acridine content in the simulated wastewater after degradation was calculated by the aforementioned high performance liquid chromatography method and the aforementioned acridine degradation rate calculation formula. Figure 5 shown.
[0083] from Figure 5 It can be seen from the graph that as the pH value increases, the degradation efficiency of acridine increases accordingly, but when the pH value is greater than 7, the degradation efficiency of acridine begins to decrease. The best degradation efficiency is achieved at pH 7, but the degradation rate can still be maintained at more than 80% after reacting for 3 h under a wide range of acidity and alkalinity conditions. It can be seen that the gC provided by the present invention 3 N 4 / HRP photoenzyme catalyst has good pH stability.
[0084] Test Example 3 Investigating the effect of reaction temperature on acridine degradation during degradation
[0085] Prepare simulated wastewater with an acridine concentration of 10 mg / L and a pH of 7. Take 15 mL of the simulated wastewater and add it to a 30 mL reactor. Then add 10 mg of gC prepared in Example 1. 3 N 4 / HRP photoenzyme catalyst, the solution was stirred for 30 min in the dark at 20°C, 30°C, 40°C, 50°C, and 60°C, 200 r / min reaction conditions to balance adsorption-desorption, and then the photocatalytic reaction was carried out under a 300W xenon lamp and a 420 nm cutoff filter for 0.5-3 hours. After the reaction, the gC 3 N 4 / HRP photoenzyme catalyst. Test results are as follows Figure 6 shown.
[0086] from Figure 6 It can be seen from the figure that as the degradation reaction temperature increases, the degradation efficiency of acridine decreases. At 20 °C, the degradation rate is 99.9% after 3 h of reaction. Based on this data, under the drive of visible light, gC 3 N 4 The photogenerated electrons, hydroxyl radicals, and superoxide anions produced by the HRP photoenzyme catalyst can all be used to degrade acridine, completely degrading acridine into CO 2 and H 2 O, so that acridine can achieve complete mineralization. Finally, the degradation efficiency can reach 99.9% within 3 hours. 3 N 4 / HRP photoenzyme catalyst can still maintain a degradation rate of more than 80% after reacting for 3 h at 60°C. 3 N 4 / HRP photoenzyme catalyst has good temperature stability.
[0087] Test Example 4 Investigation of Catalyst Degradation Cycle Stability
[0088] Prepare simulated wastewater with an acridine concentration of 10 mg / L and a pH of 7, take 15 mL of the simulated wastewater and add it to a 30 mL reactor, then add 10 mg of gC prepared in Example 1 and 3 N 4 / HRP photoenzyme catalyst, the solution was stirred for 30 min in the dark under the reaction conditions of 20 °C and 200 r / min to balance the adsorption-desorption, and then the photocatalytic reaction was carried out under a 300 W xenon lamp and a 420 nm cutoff filter for 0.5-3 h, and the gC was centrifuged and filtered. 3 N 4 / HRP photoenzyme catalyst, this process is the first cycle of degradation.
[0089] The filtered gC 3 N 4 The / HRP photoenzyme catalyst was reused in the simulated wastewater containing acridine at a concentration of 10 mg / L and a pH of 7 to degrade acridine. This process is the second cycle of degradation.
[0090] The above process was repeated for a total of 5 cycles. Finally, the degradation rate of acridine in 5 cycles was as follows: Figure 7 shown.
[0091] from Figure 7 It can be seen that gC 3 N 4After 5 cycles, the degradation rate of gC / HRP photoenzyme catalyst can still be maintained at more than 80% for 3 h. The reason for the decrease in degradation rate is probably due to the 3 N 4 / HRP photoenzyme catalyst loss during the centrifugation process. 3 N 4 / HRP photoenzyme catalyst is reusable.
[0092] The above are only preferred embodiments of the present invention. It should be pointed out that, for those skilled in the art, several modifications and improvements can be made without departing from the concept of the present invention. These should also be regarded as the protection scope of the present invention. These will not affect the effect of the implementation of the present invention and the practicality of the patent.
Claims
1. Use of a photoenzyme catalyst in photocatalytic degradation of acridine, characterized in that: The photoenzyme catalyst has a nanoflower structure, and the nanoflower structure is fixed with g-C3N4 and HRP, wherein in the photoenzyme catalyst, the mass ratio of g-C3N4 to HRP is (1.5-3):1, the nanoflower structure contains divalent copper ions and phosphate ions, and the HRP is horseradish peroxidase; The photoenzyme catalyst is prepared by the following method: Prepare a reaction mixture containing g-C3N4, HRP, and a phosphate buffer solution of a divalent copper salt, The reaction mixture is allowed to react at 0-10°C for 12-36 hours, After the reaction is completed, the photoenzyme catalyst is separated and obtained.
2. The use according to claim 1, characterized in that In the photoenzyme catalyst, the mass ratio of g-C3N4 and HRP is 1.5:
1.
3. The use according to claim 1, characterized in that In the reaction mixture, the molar concentration ratio of divalent copper ions to phosphate is 1:(15-25).
4. The use according to claim 1, characterized in that In the reaction mixture, the concentration of g-C3N4 is 0.125-0.75 mg / mL, the concentration of HRP is 0.25 mg / mL, the concentration of divalent copper ions is 10 mM, and the concentration of phosphate buffer solution is 190 mM.
